Worlds Fair St. Louis U.S.A. 1904 - Palace of Manufactures (Geo. Coldeway, Sole Agent (9992))
On card front: Gesetzlich geschtzt 9150, On card back: Printed by Lith. Institute of Rosenblart Frkf o/M, Germany.